The Impact of Teacher Training on Student Achievement in English Teaching-Learning at SMA S Nupela - Laoli, Adieli; Hia, Rizka Handayani; Maruao, Fincessia Febrianti; Gulo, Jernita; Zega, Sailas Mardianti (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2025)
This study investigates the impact of teacher training in English classes at SMA S Nupela on students' performance. The objective is to assess the impact of different training methods such as workshops, online training and peer mentoring on students' improvement in English language proficiency. The study employs a quasi-experimental design with a control and experimental group and collects primary data from teachers and students and secondary data from school records. Results show that teacher training significantly improved students' performance with the greatest improvement coming from peer mentoring (16.2%), followed by workshops (11.1%) and online training (8.1%). Statistical analysis using paired t-test confirmed that all training methods had a significant effect on students' performance (p-value < 0.05). Furthermore, the ANOVA results showed a significant difference between the training groups (F = 4.91, p-value = 0.010), suggesting that the training method has an impact on student success. This study highlights the importance of teacher training, especially interactive methods such as peer mentoring, in improving both teaching effectiveness and student outcomes in English language learning. These findings provide valuable insights for designing more effective teacher training programs to improve the quality of education in SMA S Nupela.